On believing in the church as prefiguration of the world to come - Smit, Peter-Ben (International journal of philosophy and theology, 2025)
This article focuses on the question of ‘believing in the church,’ as it is part of the Niceno-Constantinopolitan Creed. Investigating some of the problems that this article of the creed causes, it is proposed that a prefigurative understanding of the church and its qualities (one, holy, catholic, and apostolic) can both place them in proper perspective and thereby alleviate some of the theological (and spiritual) problems connected with this part of the creed.